(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nowadays, the Internet serves as a public, collaborative, and self-sustaining platform that is accessible to millions of individuals globally. The significant expansion of the Internet can be attributed to its straightforward design principles, which facilitate the widespread interconnection of diverse systems. These design principles do not include any mechanisms for a server to control the amount of traffic it receives or its sources. Consequently, Internet hosts are susceptible to network attacks such as Denial-of-Service (DoS) and Distributed-Denial-of-Service (DDoS) attacks, which have increasingly significant economic and social repercussions. One of the primary challenges facing the Internet is the issue of source IP address spoofing. In the current landscape of Internet communication, verifying the authenticity of the source of an IP packet is a critical concern. The prevalence of IP spoofing poses a threat to legitimate Internet users, prompting various researchers to explore detection and defense mechanisms against this issue.